Child-rearing During Postgraduate Medical Training and Its Relation to Stress and Burnout: Results From a Single-institution Multispecialty Survey. Issue 3 (13th February 2021) - Spruce, Marguerite W; Gingrich, Alicia A; Phares, Amanda; Beyer, Carl A; Salcedo, Edgardo S; Guralnick, Susan; Rea, Margaret M
ABSTRACT: Introduction: Child-rearing is difficult for medical trainees, but much of the available evidence is limited to individual specialties or lacks an analysis of well-being. In light of this, we sought to examine current perspectives across a wide range of medical specialties, determine associations with stress and burnout, and identify potential supportive solutions. Methods: After Institutional Review Board approval, a voluntary and anonymous survey was sent to all residents and fellows at a large academic medical center with a U.S. Air Force joint training agreement in 2019. Frequency tables were generated for survey responses, using χ 2 test for analysis between groups. Results: One hundred and eighty-four physician trainees completed the survey (21.6% response rate), of which 38.0% were parents. Overall, 90.8% of trainees want children but 68.5% plan to wait until after training to start or grow their families, mainly due to insufficient time or inadequate child care. Less than 2% cited lack of program support as the reason. Among trainee parents, 72.0% reported that child care was at least quite stressful. Child care contributes to burnout for 68.6% of trainee parents, and there was no difference between medical and surgical trainees or between military and nonmilitary trainees. Day care was the most common primary child care strategy, and 37.1% of trainee parents reported spending >25% of their household income on child care. Proposed helpful solutions include on-site day care and subsidies. Conclusions: Most medical trainees in this sample want children, yet many are delaying growing their families due to time and financial constraints. For trainee parents, child care causes stress and family and financial strain and contributes to burnout. Physicians in training, including military members training at civilian medical centers, could benefit from child care assistance in order to relieve stress, reduce burnout, and improve well-being. Furthermore, by expanding existing resources and implementing new creative solutions to the challenges of child-rearing among medical professionals, the U.S. military has an opportunity to improve members' well-being and be a model to civilian graduate medical education programs nationwide.